Verification of Turbine and Governor Model of Hydro Generator Unit for the Purpose of Load Frequency Control System Simulation - Džepčeski, Dane D; Georgijević, Nikola; Pavlović, Jelena; Arnautović, Dušan; Lukić, Sanja; Stanojčić, Vladimir; Bogdanović, Slobodan; Trišić, Dušan; Jovanović, Boris; Latinović, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
In this paper, verification of power plant component models is performed by evaluating the deviations between simulation results and test results of the component under study. The obtained deviations of the simulation results from the test results, as well as the acceptability of its value for a particular model and purpose, are determined in the process of verification. In this paper, the test results, the model and the verification procedure are presented. The basis for the model synthesis and verification are the test results derived from measurements conducted with the aim of deriving the operational performance of hydro unit R2 in PSP “Bajina Bašta” connected to the load frequency control system.